PENGARUH PADAT TEBAR TINGGI TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN LELE DUMBO (Clarias gariepinus) (The Influence of Stocking Density to The Growth of Catfish (Clarias gariepinus)) - M.Bobbie Jhora Waker; Yunasfi Djayus; Syammaun Usman (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Catfish is one of the most interest fish consumption to full fill the market demands is needed of intensive cultivation can be done by optimizing the stocking density using high stocking density system. This research aims to determine the effect of nigh stocking densities on the survival and growthrates of catfish as well as to determine the maximum stocking density of fish catfish with an average length of 5 cm and a weight of 1,2 grams. Catfish use as many as 450. The study was conducted in the laboratory cultivation of marine resources management, agricultural faculty of usu field in april – may 2015, maintance container used were aquarium size 60 cm x 40 cm x 40 cm with a water volume of 72 liters each aquarium. The meters were observed for 42 day is the survival rate of growth in weight and length daily, during the reasearch of artificial fish fed as much as 2 daily 5. During the study 10.00, 18.00. The experimental design used is Completely Randomized Design (CRD) is a stocking density of 600 tail/m³ (P1), 700 tail/m³ (P2), and 800 tail/m³ (P3) best daily 3,25% and 1,10%. Stocking density significantly affected the growth rate of the daily length and weight growth rate daily but did not significantly affect survival. Tuckey test result furtner showed significantly different treatment P3, P1 and P3 but not significantly different to P2.Keyword: Clarias gariepinus, Cathfish, Stocking density system of the growth of life